If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3(y + 5) = 0 Reorder the terms: 2y + 3(5 + y) = 0 2y + (5 * 3 + y * 3) = 0 2y + (15 + 3y) = 0 Reorder the terms: 15 + 2y + 3y = 0 Combine like terms: 2y + 3y = 5y 15 + 5y = 0 Solving 15 + 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 5y = 0 + -15 5y = 0 + -15 Combine like terms: 0 + -15 = -15 5y = -15 Divide each side by '5'. y = -3 Simplifying y = -3
| 50.4=2.5x*(15.4+x) | | 3x+1-2x-7=0 | | f(x)=2x^4+x^3-53x^2-14x+20 | | 10x-12=9x | | 12*k-13=39 | | 2-y=2-1 | | -5(-5+4w)=-15 | | 1=7t+8 | | 15+4k=-57 | | 2x+4+62=180 | | -20-13x=-371 | | 7+7b=35 | | -45=7-2p | | 19=23-4b | | Log(x+14)-log(x+6)=logx | | t-3=13 | | 13+7v=97 | | 3(x-7)=x-6 | | 105-3h=69 | | 6x+16=5x+9 | | 1.5(x-24)=13 | | f(-3)=6x^2-12 | | 4(3z-5)+9(5z+4)= | | 16=3d+1 | | 5-25x=105 | | 99=7j+1 | | x^2-5y^2=3 | | 2=3y-18-5x | | x^2-9+2xy+y+5=10 | | 67=25+6s | | -13+a=-6 | | 15-2x-7=14 |